Transcranial Direct Current Stimulation For Treatment Of Refractory Temporal Lobe Epilepsy: A Scoping Review - Abdul Wafi Ahmad Jafree; Hana Maizuliana Solehan; Abdul Aziz Marwan; Ummu Aiman Faisal; Nor Safiqah Sharil (Japan University of Health Sciences & Japan International Cultural Exchange Foundation, 2024)
Indexed by SCOPUS/ERA